Behaviorisme dalam Pembelajaran: Teori, Tokoh dan Aplikasinya - Kadek Marcha Kenargi; Anak Agung Sri Sanjiwani (PsyEcho Journal of Psychology, 2025)
This research is motivated by the importance of understanding behaviorism (perilaku) as one of the main schools in psychology that emphasizes observable and measurable behavior. The purpose of this study is to examine the history, basic principles, key figures, as well as the contributions and applications of behaviorism theory in the fields of education and psychology. The method used in this research is literature review (tinjauan pustaka), conducted systematically by identifying and evaluating various sources of scientific journals. The results show that the behaviorism theory emphasizes the relationship between stimulus (rangsangan) and response (tanggapan), as well as the importance of reinforcement (penguatan) in shaping behavior. This theory developed through the thoughts of figures such as Ivan Pavlov, B.F. Skinner, and Albert Bandura, and has greatly contributed to the development of learning strategies and behavioral therapy. The conclusion of this study affirms that behaviorism theory plays an important role in education, especially in designing structured learning processes oriented toward behavioral change. The implication of this study shows that behaviorism theory can be effectively applied in learning processes by paying attention to environmental factors and the stimuli provided.